Strengthening Dietary Diversity to Enhance the Access Dimension of Food Security: A Case Study of 24 Regencies/Cities in Sumatra Island - Robby Alexander Sirait (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2025)
The prevalence of undernourishment (PoU) across all regencies/cities on Sumatra Island remains quite high. Besides inflation, this condition can be caused by low dietary diversity. This study examines the effect of dietary diversity to access dimension of food security on 24 regencies/cities in Sumatra Island, as measured by the PoU. The research employs secondary data 24 regencies/cities over the 2021–2024 period published by BPS-Statistics Indonesia. Using a fixed-effects, we found that dietary diversity (particularly the diversification of carbohydrate energy sources) have a negative effect and statistically significant to PoU. Thus, dietary diversity will increase access dimension of food security. Another finding is that inflation have positive effect to PoU and the majority of carbohydrate energy source diversification consumption on Sumatra Island is still low. These findings suggest that regency/city governments can uses dietary diversity startegy and control inflation to reduce the PoU and improve access dimension of food security.